Palliative Hypofractionated Radiotherapy in Advanced Squamous Cell Carcinoma of Head and Neck - Gautam, Deepa; Shah, Arati (Nepalese Journal of Cancer, 2020)
Introduction: A significant proportion of patients with advanced squamous cell carcinoma of head and neck (HNSCC) are unsuitable for radical treatment and we aim to evaluate the acute toxicity, symptom relief and disease response after palliative hypo fractionated radiotherapy in such patients. Methods: A prospective observational study was conducted from November 2014 to November 2015 at the Department of Radiation Oncology, B.P. Koirala Memorial Cancer Hospital, Bharatpur in 30 patients with stage III or stage IV HNSCC who received radiotherapy of 30 Gy in 10 fractions over two weeks. Pain, dysphagia, insomniaand dyspnoea at presentation were assessed using 11 point numerical scale. Acute treatment toxicities we reassessed using Common Terminology Criteria for Adverse Events (CTCAE) at the end of two weeks. After six weeks of completion of radiotherapy, percentage of symptom relief and disease response based on Response Evaluation Criteria in Solid Tumors (RECIST) were recorded. A few patients were selected for further curative radiotherapy. Results: Common symptoms were pain (86.7%) and dysphagia (50%). Two-third of patients with pain and dysphagia, and about 90% patients with dyspnoea and insomnia had more than 75% symptom relief. An objective response rate of 70% and disease progression of 13.3% were observed. Acute radiation toxicities were acceptable with no grade 3 or 4 toxicities. It was observed that 46.3% of patients had mucositis, 13.3% had dysphagia, and 6.7 % had hoarseness and dermatitis each. Conclusion: Palliative radiotherapy is a suitable modality of treatment for patients with advanced HNSCC for symptom relief and tumour control, with acceptable toxicity.